Níveis de energia metabolizável e lisina digestível para frangos de corte - Meza, Sharon Karla Lüders (2013)
Two experiments were conducted to evaluate the effects of levels of metabolizable energy (ME) and digestible lysine (DL) in the diet of growing and finishing in broilers from 21- 42 days and 35-49 days, respectively, on performance characteristics, deposition rate of protein and fat, carcass yield and morphometry of the intestinal mucosa of broilers. In the first experiment, the objective was to evaluate the effect of levels of energy and digestible lysine on broilers from 21 to 42 days of age, on performance, carcass yield and intestinal morphometric characteristics. We used 768 broilers, weighing 700 grams on average, distributed in a completely randomized way and in a 4x4 factorial, four levels of ME (2800, 2950, 3100 and 3250 kcal.kg-1) and four levels of DL (0.900, 1.000, 1.100 and 1.200%), resulting in 16 treatments with three replicates and 16 birds per pen. There was an interaction (P <0.05) between the levels of ME and DL for average weight and weight gain of broilers. The greatest weight gain was obtained for the level of 1.000% digestible lysine and 3,250 kcal.kg-1 ME. The feed conversion and feed intake decreased (P<0.05) as the levels of ME and DL increased in the diets. The different levels of digestible lysine increased linearly (P<0.05) the carcass yield of broilers at 42 days, while the metabolizable energy level had no effect (P>0.05) on this variable. There was no interaction between levels studied on the yield of breast, thigh and drumstick, wings and legs. There was an interaction (P<0.05) levels of ME and DL studied on the villi of the jejunum and villus: crypt depth of the jejunum. The crypt depth of the ileum decreased linearly with increased levels of lysine and villus: crypt depth of the ileum showed a quadratic effect for the energy levels in the diet. For the villi, crypt and villus: for the crypt depth of the duodenum there was no interaction (P>0.05) in the levels studied. In the second experiment the objective was to evaluate the effect of levels of energy and digestible lysine on performance of broilers from 35 to 49 days of age, carcass yield, protein deposition rate and carcass fat, and morphometry of the intestinal mucosa. We used 768 broiler chickens of 49 days of age, with an average weight of 1,700 g, randomly distributed in 48 pens in a 4x4 factorial design with four levels of ME (3000, 3120, 3240, and 3360 kcal.kg-1) and four levels of DL (0.800, 0.900, 1.000 and 1.100%) for a total of 16 treatments with three replicates each. There was an interaction (P<0.05) between the levels of energy and digestible lysine for all performance variables studied. The highest level of lysine studied (1.100%) showed the best performance of broilers from 35 to 49 days old. The energy levels estimated for higher final weight and weight gain were 3138, 3136 kcal.kg-1 in the diet, respectively. The indicated level of 3375 is kcal.kg-1 EM in order to have better feed, both for the level of 1.100% digestible lysine. For the morphometric characteristics of the duodenal villus, height and crypt depth in the ileum obtained better results with low levels of ME and DL. The different levels of energy and digestible lysine had no influence on (P>0.05) carcass yield, cuts (breast, drumstick, thigh and wing) and abdominal fat. Likewise, there was no interaction between the levels studied on the variables mentioned. The levels of energy and digestible lysine contained in the diets of broilers from 35 to 49 days of age do not interfere in the carcass and amount of fat. There was an interaction (P<0.05) between the levels of energy and digestible lysine on the rate of protein deposition (PDR), rate of fat deposition (FDR) and fat (F) in the carcass of broilers